Penerapan Model Pembelajaran Kooperatif Tipe Fishbowl Untuk Meningkatkan Keaktifan dan Hasil Belajar IPAS pada Murid Kelas V SD Inpres Panciro Kecamatan Bajeng Kabupaten Gowa - Wahyuni, Citra; Yunus, Muh; Iskandar, Arifuddin (CV. Rayyan Dwi Bharata, 2025)
This research is a classroom action research that aims to increase interest and learning outcomes of social studies through the application of a Fishbowl-type cooperative learning model in grade V students of SD Inpres Panciro, Bajeng District Gowa Regency. The subject of this study is a grade V student of SD Inpres Panciro, Bajeng District, Gowa Regency with a total of 15 students, consisting of 8 male students and 7 female students. This research was carried out in two cycles, namely cycle I which was carried out 3 meetings (the first and second meetings for the learning process and the third meeting for the assessment of science and science learning outcomes) and cycle II was also carried out 3 meetings. The two cycles were carried out for 2 months plus summarizing all existing research results. The results of the study show that the application of the Fishbowl type cooperative learning model has succeeded in significantly increasing student learning activity. In the first cycle, the student's learning activity was recorded at only 69%, which shows that most students have not shown maximum participation in the learning process. However, after the implementation of improvements in cycle II, student learning activity has increased significantly, reaching 89%. This shows an increase in student involvement and enthusiasm in participating in learning activities, which can be caused by the use of a more interesting and effective learning model in cycle II. The Fishbowl-type cooperative learning model has also proven to be very effective in improving student learning outcomes in science and science subjects. In the first cycle, the completeness of student learning only reached 47% with an average score of 66, which indicates that many students have not reached the expected competency standards. However, in the second cycle, there was a very significant increase with learning completeness increasing to 93% and the average student score rising to 84. This increase shows that the efforts made to improve learning strategies have a positive impact so that students are better able to understand the material and achieve better learning outcomes.